2022
DOI: 10.3390/ijerph19042377
|View full text |Cite
|
Sign up to set email alerts
|

Differential Metabolites and Metabolic Pathways Involved in Aerobic Exercise Improvement of Chronic Fatigue Symptoms in Adolescents Based on Gas Chromatography–Mass Spectrometry

Abstract: Studies have found that the prevalence of chronic fatigue syndrome (CFS) in adolescents has continued to increase over the years, affecting learning and physical health. High school is a critical stage for adolescents to grow and mature. There are inadequate detection and rehabilitation methods for CFS due to an insufficient understanding of the physiological mechanisms of CFS. The purpose of this study was to evaluate the effect and metabolic mechanisms of an aerobic running intervention program for high scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…25,26,28,40,52,53 In 2022, 18 studies used a traditional non-targeted metabolomics assay. 18,24,30,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Perhaps the most thought-provoking exercise metabolomics publication from 2022 came from the Long Lab at Stanford University and was published in Nature. This study identified an exercise-induced metabolite, namely N-lactoylphenylalanine (Lac-Phe), to be associated with reduced dietary intake.…”
Section: Metabolomicsmentioning
confidence: 99%
See 3 more Smart Citations
“…25,26,28,40,52,53 In 2022, 18 studies used a traditional non-targeted metabolomics assay. 18,24,30,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Perhaps the most thought-provoking exercise metabolomics publication from 2022 came from the Long Lab at Stanford University and was published in Nature. This study identified an exercise-induced metabolite, namely N-lactoylphenylalanine (Lac-Phe), to be associated with reduced dietary intake.…”
Section: Metabolomicsmentioning
confidence: 99%
“…In 2022, 18 studies used a traditional non‐targeted metabolomics assay 18,24,30,83–97 . Perhaps the most thought‐provoking exercise metabolomics publication from 2022 came from the Long Lab at Stanford University and was published in Nature .…”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] The prevalence of CFS is estimated to be between 1% and 2% globally, causing a serious burden on the work and life of patients. [7,8] It is reported that at least 1 million people in the United States have CFS and that it is three to four times more common in women than in men, with the highest prevalence in people aged 40 to 50 years, but children and adolescents are also at risk. [9] And it has a huge impact on the American economy, costing approximately $9 to 37 billion in lost productivity and $9 to 14 billion in direct medical costs annually.…”
Section: Introductionmentioning
confidence: 99%